Metal-binding particles enhance germination and radicle tolerance index of the metallophyte grass Astrebla lappacea Lindl. Under phytotoxic lead and zinc conditions - Rossato, L; Pudmenzky, A; Doley, D; Monteiro, M; Whittaker, M; Schmidt, S; Macfarlane, J; Baker, AJM (Mine Closure 2009: Fourth International Conference on Mine Closure, 2009)
Metal-contaminated soils often lack effective vegetation cover and are consequently prone to disturbance and in some cases leaching. The establishment of self-sustaining plant cover on contaminated sites often requires a reduction in available metal concentrations in the rooting zone. In theory, hydrogel particles have the potential to improve plant establishment rates and site rehabilitation by: (i) detoxifying the soils in terms of heavy metal ‘capture’ and providing a source of water for plants during germination and establishment; (ii) allowing the establishment of selected metal tolerant plants (metallophytes) at high soil metal concentrations and under drought; and (iii) by acting in synergy with the sequestration of metals by metallophytes, to achieve phytostabilisation of contaminated sites and reduce the risks of uncontrolled metal transfers into the environment via wind and water erosion. Various micron- and nano-sized metal-binding cross-linked acrylamide polymer hydrogel particles were synthesised and tested in laboratory-scale experiments in order to determine: (i) the capacity of particles to sequester heavy metals (lead (Pb), zinc (Zn), copper (Cu) and the metalloid arsenic (As)) in solution at high soluble concentrations; (ii) the water-holding capacity of the particles; and (iii) the effect of particle treatment on the in vitro germination percentage and radicle tolerance index (RTI at 2 days) of an Australian metallophyte grass (Astrebla lappacea Lindl.) in the presence of high solution concentrations of heavy metals normally phytotoxic to that species. The results show that one micron-sized thiol functional cross-linked acrylamide polymer hydrogel (X3) significantly reduced the available solution concentrations of Pb (9,650 µM), Cu (4,000 µM) and Zn (10,000 µM) by 86.5%, 75.5% and 63.8% respectively. Arsenic (667 µM) was excluded from the polymer network. This polymer could hold deionised water up to 607.8% (6.1 times) of its dry mass. Alone, it enhanced seed germination, and at otherwise phytotoxic Pb (9,650 µM) and Zn (10,000 µM) solution concentrations it allowed normal germination rates and increased radicle elongation rates of A. lappacea. The polymer may have potential for use in the restoration of contaminated land by reducing soil solution concentrations of metal cations, and improving plant germination rates through a combination of reduced toxicity and increased soil-water availability. Future research will address whether the particles are as effective in binding to heavy metals in contaminated substrata, increasing the volume of soil solution water available to plants and improving plant establishment. Metal-binding particles enhance germination and radicle tolerance index of the metallophyte L. Rossato et al. grass Astrebla lappacea Lindl. under phytotoxic lead and zinc conditions 302 Mine Closure 2009, Perth, Australia